Pengaruh Meniran (Phyllanthus niruri L) Terhadap Patogenesis lnfeksi Salmonella - Sunarno, Sunarno (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2009)
Typhoid/paratyphoid disease is a major problem in Indonesia. Management of therapy including the use of immunomodulator must be developed continuously. In this case Phyllanthus niruri L is immunomodulator that has been useﬁtl to increase the animal and human immunity. The purpose of this stun) was to know the inﬂuence of Phyllanthus niruri L on the Salmonella infection focusing on spleen bacterial colonies. The experiment was designed with post test-only control group to 18 Bab/C Mice infected by Salmonella typhimurium divided into one control group and two experimental groups which hmie given Phyllanthus niruri L of 3x 0.125 mg/day (P1) and 3x 0.25 mg/day (P2) orally. Statistical analysis was used Oneway ANOVA test. The research result showed that treatmen P1 had significant inﬂuence to decrease spleen bacterial colonies compared to control group.